2002
DOI: 10.1126/science.1068186
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Basis of Proton Motive Force Generation: Structure of Formate Dehydrogenase-N

Abstract: The structure of the membrane protein formate dehydrogenase-N (Fdn-N), a major component of Escherichia coli nitrate respiration, has been determined at 1.6 angstroms. The structure demonstrates 11 redox centers, including molybdopterin-guanine dinucleotides, five [4Fe-4S] clusters, two heme b groups, and a menaquinone analog. These redox centers are aligned in a single chain, which extends almost 90 angstroms through the enzyme. The menaquinone reduction site associated with a possible proton pathway was also… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
436
2
2

Year Published

2004
2004
2015
2015

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 474 publications
(448 citation statements)
references
References 26 publications
8
436
2
2
Order By: Relevance
“…The coordination sphere of the molybdenum (or tungsten) center was completed with a sulfur atom, and a SeCH 3 group that was chosen to mimic the SeCys 140 residue. The model was subsequently completed with the conserved His 141 , Arg 333 , and Val 139 residues (amino acid numbering corresponding to E. coli Fdh-H) [4,6,7,12,13]. Conventional protonation states for all amino acids at pH 7 were adopted and the carboxylate and the amino groups of the terminal amino acids of each chain of the model were protonated.…”
Section: Theoretical Calculationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The coordination sphere of the molybdenum (or tungsten) center was completed with a sulfur atom, and a SeCH 3 group that was chosen to mimic the SeCys 140 residue. The model was subsequently completed with the conserved His 141 , Arg 333 , and Val 139 residues (amino acid numbering corresponding to E. coli Fdh-H) [4,6,7,12,13]. Conventional protonation states for all amino acids at pH 7 were adopted and the carboxylate and the amino groups of the terminal amino acids of each chain of the model were protonated.…”
Section: Theoretical Calculationsmentioning
confidence: 99%
“…The crystal structures of three of these enzymes have been reported. The molybdenumcontaining enzymes are Fdh-H and the membrane-bound Fdh-N from Escherichia coli K12 [4][5][6][7][8][9][10]. The tungstencontaining enzyme is the periplasmic Fdh from the sulfatereducing bacterium Desulfovibrio gigas [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…The Mo-containing enzymes are the Fdh-H from Escherichia coli [17], which is one of the components of the formate hydrogen lyase complex in E. coli, and the recently reported membrane-bound Fdh-N from E. coli, which is supposed to participate in the redox loop of the proton motive force generation across the membrane cell [18]. The W-containing enzyme is the Fdh from the sulfate-reducing bacterium (SRB) Desulfovibrio gigas [19,20].…”
mentioning
confidence: 99%
“…The W-containing enzyme is the Fdh from the sulfate-reducing bacterium (SRB) Desulfovibrio gigas [19,20]. E. coli Fdh-H is a monomeric enzyme (79 kDa), while the E. coli Fdh-N is an abc heterotrimer with subunits of 113, 32, and 21 kDa, respectively [18]. The W-Fdh from D. gigas is a heterodimeric enzyme with 92 and 29 kDa subunits, respectively (Fig.…”
mentioning
confidence: 99%
“…Further analysis showed that these are more similar to cytochrome b561-like sequences as discussed below (section 3.5, Figure S5). (Berks et al, 1995, Jormakka et al, 2002.…”
Section: Cytochrome-b Of the B 6 F And The Bc Complexmentioning
confidence: 99%